Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18632/oncotarget.8132
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of activating cancer mutations in FGFR kinases and their differential responses to inhibitors in clinical use

Abstract: Frequent genetic alterations discovered in FGFRs and evidence implicating some as drivers in diverse tumors has been accompanied by rapid progress in targeting FGFRs for anticancer treatments. Wider assessment of the impact of genetic changes on the activation state and drug responses is needed to better link the genomic data and treatment options. We here apply a direct comparative and comprehensive analysis of FGFR3 kinase domain variants representing the diversity of point-mutations reported in this domain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 56 publications
5
89
0
Order By: Relevance
“…The observation that all three FGFR2-fusion+ ICC patients developed secondary FGFR2 kinase domain mutations, with multiple mutations emerging in two patients, suggests that these alterations are major drivers of clinical resistance to FGFR inhibition. The p.V564 gatekeeper mutation, which was common to all three patients, and the additional six FGFR2 point mutations identified were predicted to confer resistance by previous in vitro studies and structural modeling (22-26). These findings may have more general significance since equivalent FGFR2 point mutations exist de novo in many cancers (26).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The observation that all three FGFR2-fusion+ ICC patients developed secondary FGFR2 kinase domain mutations, with multiple mutations emerging in two patients, suggests that these alterations are major drivers of clinical resistance to FGFR inhibition. The p.V564 gatekeeper mutation, which was common to all three patients, and the additional six FGFR2 point mutations identified were predicted to confer resistance by previous in vitro studies and structural modeling (22-26). These findings may have more general significance since equivalent FGFR2 point mutations exist de novo in many cancers (26).…”
Section: Discussionmentioning
confidence: 76%
“…The p.V564 gatekeeper mutation, which was common to all three patients, and the additional six FGFR2 point mutations identified were predicted to confer resistance by previous in vitro studies and structural modeling (22-26). These findings may have more general significance since equivalent FGFR2 point mutations exist de novo in many cancers (26). Moreover, FGFR3 fusions are present in several malignancies, including glioblastoma multiforme, urothelial carcinoma, and lung adenocarcinoma (27), and our in vitro data suggest that mutations affecting corresponding amino acids in FGFR3 may cause resistance to FGFR inhibitors in this context.…”
Section: Discussionmentioning
confidence: 76%
“…FGFR3 N540 and K650 mutations, a gatekeeper mutation (FGFR3 V555M), and other mutations corresponding to FGFR3 I538V, FGFR2 N549H/T, FGFR2 K659N, FGFR1 V651M, FGFR4 V550L and V550E (typical in Rhabdomyosarcoma) and FGFR4 V550M (in breast cancer) are the most common alterations. In the future, it should be done more studies to reveal differential, drug-specific impact of different FGFR KD (Kinase Domain) mutations (Patani et al, 2016). Similarly to MET amplifation, an activation of EGFR has been identified in FGFR3-mutant bladder cancer as a mechanism of resistance.…”
Section: Resistance To Therapiesmentioning
confidence: 99%
“…Compounds 11-28 were prepared with a similar procedure as that used for 8. [2,3-b] [2,3-b]pyrazine (11) [2,3-b]pyrazine (14). [2,3-b]pyrazine (15) [2,3-b]pyrazine (16) [2,3-b]pyrazine (17 [2,3-b]pyrazine (18 …”
Section: Chemistrymentioning
confidence: 99%
“…Currently, several FGFR-targeted agents, mostly are small molecules binding to the kinase domain, are evaluated in clinical trials for cancer treatment, and most intriguing and advanced evaluated are FGFR-selective inhibitors, such as AZD4547 (1) [11], NVP-BGJ398 (2) [12] and JNJ-42756493 (3) [13]. As investigated by Patani et al [14], due to the landscape of activated mutations in FGFR kinases, the above-mentioned FGFR inhibitors (1, 2, 3) showed distinct effects towards different mutants, which indicated that developing FGFR inhibitors with novel scaffold are highly demanded as they may provide unique therapeutic benefits towards certain patients. In the development of tyrosine kinase inhibitors, we previously synthesized a series of 1-sulfonylpyrazolo [4,3-b]pyridinesas potent and selective c-Met inhibitors [15].…”
Section: Introductionmentioning
confidence: 99%